Minimal Realization Plus Current Output CC-based Biquad Circuit - Sompong Wisetphanichkij; Krit Angkeaw; Napat Sra-ium (ECTI Transactions on Electrical Engineering Electronics and Communications, 2024)
This paper presents a minimal design of a biquad circuit using only one plus current output type-II current conveyor (CCII), one differential voltage current conveyor (DVCC) and grounded passive components. The circuit enables the implementation of all 5 basic filter types: low-pass (LP), band-pass (BP), high-pass (HP), band-stop (BS) and all-pass (AP) by the selecting and adding of the input and output currents with no component matching constraints. Moreover, the circuit parameters ω0 and Q can be set simply by adjusting the circuit components. The proposed biquad circuit performance has very low sensitivity to circuit components due to its simple structure and a small number of devices (2 active and 4 grounded passive components). This allows the circuit to work at high frequencies. The performance of the proposed topology was evaluated through PSPICE simulator using the 0.18 mm CMOS technology from the Taiwan Semiconductor Manufacturing Company (TSMC).
Keywords: Low-power high-performance VLSI design; Quantum Computing Algorithms and Architecture